Diabetes distress among immigrants of south Asian descent living in New York City: baseline results from the DREAM randomized control trial - Farhan Mohsin; Laura Wyatt; Hayley Belli; Shahmir Ali; Deborah Onakomaiya; Supriya Misra; Yousra Yusuf; Shinu Mammen; Jennifer Zanowiak; Sarah Hussain; Haroon Zafar; Sahnah Lim; et al. (BMC Public Health)
Abstract Background Type 2 diabetes (T2D) disproportionately affects individuals of South Asian descent. Additionally, diabetes distress (DD) may lead to complications with diabetes management. This study examines the prevalence of DD among foreign-born individuals of South Asian descent in New York City (NYC) and its association with sociodemographic and clinical factors. Methods Baseline data was collected from the Diabetes Research, Education, and Action for Minorities (DREAM) Initiative, an intervention designed to reduce hemoglobin A1c (HbA1c) among South Asian individuals with uncontrolled T2D at primary care practices in NYC. The Diabetes Distress Scale (DDS) measured DD, and Core Healthy Days Measures assessed physical and mental healthy days. Sociodemographic variables were analyzed using descriptive statistics, Chi-square tests assessed categorical variables, and Wilcoxon Rank Sum tests evaluated continuous variables (Type I error rate = 0.05). Logistic regression models examined associations between HbA1c, mental health, and other covariates with dichotomized DD subscales. Results Overall, 414 participants completed the DDS at baseline (median age = 55.2 years; SD = 9.8). All were born outside of the US; the majority were born in Bangladesh (69.8%) followed by India, Pakistan, and Nepal (24.7%) and Guyana and Trinidad and Tobago (5.5%). High emotional burden, regimen-related distress and physician-related distress were reported by 25.9%, 21.9%, and 6.2% of participants, respectively. In adjusted analyses, individuals with ≥ 1 day of poor mental health had higher odds of overall distress (OR:3.8, p = 0.013), emotional burden (OR:4.5, p < 0.001), and physician-related distress (OR:4.6, p = 0.007) compared to individuals with no days of poor mental health. Higher HbA1c (OR:1.45, p = < 0.001) was associated with regimen-related distress; and lower emotional support was associated with overall distress (OR:0.92, p < 0.001) and regimen-related distress (OR:0.95, p = 0.012). Individuals born in Bangladesh had significantly lower odds of overall distress, emotional burden, and regimen-related distress compared to individuals born in Guyana and Trinidad and Tobago. Conclusions Findings highlight the rate and risk factors of DD among individuals of South Asian descent living in NYC. Screening for DD in patients with prediabetes or diabetes should be integrated to address mental and physical health needs. Future research can benefit from a longitudinal analysis of the impact of DD on diabetes self-management and health outcomes. Trial registration This study uses baseline data from “Diabetes Management Intervention for South Asians” (NCT03333044), which was registered with clinicaltrials.gov on 6/11/2017.